Development and in vitro evaluation of solid dispersions as strategy to improve albendazole biopharmaceutical behavior - Simonazzi, Analía (2018)
Solid dispersions using Poloxamer 407 as carrier were developed to improvealbendazole (ABZ) solubility and dissolution profiles. ABZ/poloxamer solid dispersions were prepared, and dissolution profiles were mathematically modeled and compared with physical mixtures, pharmaceutical ABZ and a commercial formulation. Results: Poloxamer 407 increased exponentially ABZ solubility, in about 400% when 95% w/w of polymer compared with its absence. Solid dispersions initial dissolution rate was three to 20-fold higher than physical mixtures, the drug and the commercial formulation. All the solid dispersions required less than 2.2 min to reach an 80% of ABZ dissolution, while the commercial formulation needed around 40 min. Conclusion: Solid dispersions improved ABZ solubility and dissolution rate, which could result in a faster absorption and an increased bioavailability.